2004
DOI: 10.1111/j.1432-1033.2004.04251.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of selenium compounds with zinc finger proteins involved in DNA repair

Abstract: As an essential element, selenium is present in enzymes from several families, including glutathione peroxidases, and is thought to exert anticarcinogenic properties. A remarkable feature of selenium consists of its ability to oxidize thiols under reducing conditions. Thus, one mode of action recently suggested is the oxidation of thiol groups of metallothionein, thereby providing zinc for essential reactions. However, tetrahedral zinc ion complexation to four thiolates, similar to that found in metallothionei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 61 publications
2
76
0
Order By: Relevance
“…We recognize that further analyses in a larger population and a wider range of antioxidant capacities are required for confirmation of our findings. In support of our observations a similar correlation between 8-oxo-dG in leukocytes and OGG1 genotype has been made by Tarng et al (79) (80) has reported that activity of the DNA repair protein XPA is modulated by redox modification to a zinc finger motif present in its active site. In addition, reduced repair capacity of variant OGG1 protein only under conditions of oxidative stress would explain why no difference between background levels of oxidative DNA damage was observed between the three groups.…”
Section: Discussionsupporting
confidence: 79%
“…We recognize that further analyses in a larger population and a wider range of antioxidant capacities are required for confirmation of our findings. In support of our observations a similar correlation between 8-oxo-dG in leukocytes and OGG1 genotype has been made by Tarng et al (79) (80) has reported that activity of the DNA repair protein XPA is modulated by redox modification to a zinc finger motif present in its active site. In addition, reduced repair capacity of variant OGG1 protein only under conditions of oxidative stress would explain why no difference between background levels of oxidative DNA damage was observed between the three groups.…”
Section: Discussionsupporting
confidence: 79%
“…Se-induced activation of p53 is also dependent on the BRCA1 protein in recombinational repair, which is frequently mutated in familial breast cancer (55). It also was reported that Se inhibited DNA-binding activity of transcription factors such as AP-1, NF-kB, SP-1, and SP-3, as well as the DNA-repair proteins XPA in the NER pathway and formamidopyrimidine DNA glycosylase (FPG) in the BER pathway (27,76,131,195). These data imply that Se may reduce cancer incidence through modulating DNA repair, redox status of cells, and the cellular transcriptional response to oxidative stress.…”
Section: A Dietary Antioxidantsmentioning
confidence: 99%
“…Such a fact indicates a signifi cant association between Zn and Se homeostasis. Moreover, a number of fundamental studies have investigated a chemical basis of this association (Blessing et al, 2004;Feroci et al, 2005). Earlier studies have indicated the possibility of mutual infl uence of zinc and selenium in the case of supplementation.…”
Section: Introductionmentioning
confidence: 99%